The global, regional, and national burden of pancreatic cancer and its attributable risk factors in 195 countries and territories, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017 - Pourshams, Akram; Sepanlou, Sadaf G; Ikuta, Kevin S; Bisignano, Catherine; Safiri, Saeid; Roshandel, Gholamreza; Sharif, Mehdi; Khatibian, Morteza; Fitzmaurice, Christina; Nixon, Molly R; Abbasi, Nooshin; Afarideh, Mohsen; et al. (The Lancet Gastroenterology & Hepatology, 2019)
Background: Worldwide, both the incidence and death rates of pancreatic cancer are increasing. Evaluation of pancreatic cancer burden and its global, regional, and national patterns is crucial to policy making and better resource allocation for controlling pancreatic cancer risk factors, developing early detection methods, and providing faster and more effective treatments. Methods: Vital registration, vital registration sample, and cancer registry data were used to generate mortality, incidence, and disability-adjusted life-years (DALYs) estimates. We used the comparative risk assessment framework to estimate the proportion of deaths attributable to risk factors for pancreatic cancer: smoking, high fasting plasma glucose, and high body-mass index. All of the estimates were reported as counts and age-standardised rates per 100 000 person-years. 95% uncertainty intervals (UIs) were reported for all estimates. Findings: In 2017, there were 448 000 (95% UI 439 000–456 000) incident cases of pancreatic cancer globally, of which 232 000 (210 000–221 000; 51·9%) were in males. The age-standardised incidence rate was 5·0 (4·9–5·1) per 100 000 person-years in 1990 and increased to 5·7 (5·6–5·8) per 100 000 person-years in 2017. There was a 2·3 times increase in number of deaths for both sexes from 196 000 (193 000–200 000) in 1990 to 441 000 (433 000–449 000) in 2017. There was a 2·1 times increase in DALYs due to pancreatic cancer, increasing from 4·4 million (4·3–4·5) in 1990 to 9·1 million (8·9–9·3) in 2017. The age-standardised death rate of pancreatic cancer was highest in the high-income super-region across all years from 1990 to 2017. In 2017, the highest age-standardised death rates were observed in Greenland (17·4 [15·8–19·0] per 100 000 person-years) and Uruguay (12·1 [10·9–13·5] per 100 000 person-years). These countries also had the highest age-standardised death rates in 1990. Bangladesh (1·9 [1·5–2·3] per 100 000 person-years) had the lowest rate in 2017, and São Tomé and Príncipe (1·3 [1·1–1·5] per 100 ...